UTILIZATION OF DIGITAL LITERACY IN HISTORY LEARNING AS A TEACHER'S EFFORT TO IMPROVE STUDENTS' CRITICAL THINKING - Astrini Eka Putri (Jurnal Scientia, 2023)
The article aims to describe how to utilize digital literacy in history learning as a teacher's effort in improving students' critical thinking. The research method used in writing this article is a literature study. Analysis involves evaluating research approaches, methods, and results that have been reported in related literature. The results and discussion of this article are as follows: the use of digital literacy as an innovative strategy for teachers to improve students' critical thinking. Digital literacy includes the ability to access, evaluate, and participate in digital content, becoming essential skills in today's information age. History learning that uses digital literacy can optimize the learning process by providing access to digital resources, teaching criticality in assessing information, and utilizing multimedia to improve understanding of historical content. Teachers need to teach how to access relevant digital resources, develop critical skills in information assessment, and teach multimedia analysis. The implementation of digital literacy not only enriches historical understanding, but also equips students with the skills needed in a digital society. This literature study analyzes best practices and the contribution of digital literacy to improving critical thinking in the context of history learning.